Flipping tropes & subverting stereotype priming in the hunger games trilogy - Raihanah M. M.,; Ruzy Suliza Hashim,; Adzura Elier, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This is a review paper on the apparent force of commercial success and social media presence being a key in the changes of female representation in popular culture using The Hunger Games dystopian trilogy’s global commercial success and its impact as case in point. It argues that the trilogy’s commercial success is valuable in helping normalise the flipped gender roles or subverting the stereotypical gender primes. While dystopian literature supposedly features worlds and societies beyond typical real-life rules, many parts of that fictional world will still exhibit traits and beliefs contemporary to its author and resonate with its audience. The normalisation of gender stereotypes can often be seen in characters and social dynamics portrayed repeatedly throughout other forms of media communication. These and other literary works carry within it these stereotypical traits or behaviours a shorthand frame of reference which are called tropes. In this paper, the tropes are viewed through the sociological lens called stereotype priming which is the perpetuation of stereotypes through systemic means targeting certain behaviours, traits or beliefs. This paper looks at instances of tropes exhibiting priming functions within the dystopian world of not just The Hunger Games trilogy and how the commercial success of the empowered female has paved the way for more positive female representation in popular media culture since then. This lens has been expanded to take into account how The Hunger Games trilogy continues to have relevance post-pandemic regarding issues that current facts have brought dangerously close to dystopian fiction.